Strategies For Increasing The Capacity Of Tourism Organizations And Community Participation In Lamajang Village, Pangalengan District, Bandung Regency - Sakti Ferdinand Akanda Negara; Deden Syarifuddin; Furi Sari Nurwulandari (Jurnal Scientia, 2024)
Tourism organizations and community participation play a key role in the development of Desa Wisata. This research is basically formulated to increase the reach of tourism destination management and development by community-based tourism organizations that actually already exist in the research locus, namely the Tourism Awareness Group or Pokdarwis. The purpose of the research is to solve the tourism problem of Lamajang Village because it has not yet experienced an increase in the status of the village which was previously a tourist village without a description as stated in the Decree of the Bandung Regent No.556.42/Kep/72-Dispopar/2011 concerning the Determination of Tourism Villages in the Bandung Regency Region, then in 2022 it became a pilot village in the year stated in the Decree of the Bandung Regent No.556/Kep.770-Disbudpar/2022 concerning the Determination of Tourism Villages in the Bandung Regency Region. The research method used is SWOT analysis with an organizational management point of view according to Gullick (in Setyawati, 2016), namely POSDCoRB (planning, organizing, directing, coordinating, reporting, budgeting). The results of this study show that the Pokdarwis strategy has not organized the tourism organization effectively, so the conclusion of this study is to formulate a work program plan that supports the goals of the Village Government, increase the leadership capacity of the Pokdarwis Chairperson in the aspect of human resource management, provide training to the post-acceptance organizational board and conduct post-training restructuring according to the board qualification process, prioritize the internal objective view of the organization, document the organization's performance and financial reports, empower people who are already actively involved in tourism activities, then the Village Government together with Pokdarwis collaborate to take a persuasive approach with the community. and encourage the community to be actively involved in tourism activities in the context of economic empowerment.